Guts & glory : the American Civil War - Thompson, Ben, 1980- (Little, Brown and Company, 2014)
An educational collection of amazing-but-true facts about the Civil War shares accounts of such events as female spies fighting for the Rebel cause, cavalry rides in enemy territory, and the reelection of President Lincoln.